H2-driven xylitol production in Cupriavidus necator H16 - Tytti Jämsä; Nico J. Claassens; Laura Salusjärvi; Antti Nyyssölä (Microbial Cell Factories)
Abstract Background Biocatalysis offers a potentially greener alternative to chemical processes. For biocatalytic systems requiring cofactor recycling, hydrogen emerges as an attractive reducing agent. Hydrogen is attractive because all the electrons can be fully transferred to the product, and it can be efficiently produced from water using renewable electricity. In this article, resting cells of Cupriavidus necator H16 harboring a NAD-dependent hydrogenase were employed for cofactor recycling to reduce d-xylose to xylitol, a commonly used sweetener. To enable this bioconversion, d-xylose reductase from Scheffersomyces stipitis was heterologously expressed in C. necator. Results d-xylose reductase was successfully expressed in C. necator, enabling almost complete bioconversion of 30 g/L of d-xylose into xylitol. It was found that over 90% of the energy and protons derived from hydrogen were spent for the bioconversion, demonstrating the efficiency of the system. The highest xylitol productivity reached was 0.7 g/L/h. Additionally, the same chassis efficiently produced l-arabitol and d-ribitol from l-arabinose and d-ribose, respectively. Conclusions This study highlights the efficient utilization of renewable hydrogen as a reducing agent to power cofactor recycling. Hydrogen-oxidizing bacteria, such as C. necator, can be promising hosts for performing hydrogen-driven biocatalysis.